Comparación de los efectos de dos técnicas de electroanalgesia en la enfermedad articular degenerativa tarsometatarsiana del equino - García Liñeiro, J.A. (2006)
A clinical model was designed in order to compare the analgesic effects of TENS (transcutaneous electrical neuromuscular stimulation) and RAME (reflex action mechanical electrostimulation), since both methods have been proven effective in equine medicine. The clinical model consisted of 10 horses with a standardized diagnostic protocol of tarsometatarsial degenerative joint disease; these were subjected to both treatments with an interval of 6 months, then results were compared. Treatments were performed every day and the clinic evaluation every two days (five controls). The clinic parameters considered were: a- straight and circle trot, in hard and soft surface. b- Tarsus Flexion test c- Tarsus Test (Churchill test). McNemar?s test was performed in order to compare lameness and forced flexion tests at ?control 5? stage, after applying TENS and RAME treatments; no significant differences were found between both treatments (p=0,2568). The Mc Nemar?s test also used to compare tarsal flexion tests (Churchill?s Test) after TENS and RAME treatments, showed no significant differences between Both (p=0,7055). It was therefore\nconcluded that there is little difference between the two methods, while there is an important decrease as from ?control 2?. This situation lets us assume that both methods may be used indistinctly in an effective manner, choosing to use one or the other according to the advantages and disadvantages of its applications.